Inter‐ethnic differences in pharmacokinetics-is there more that unites than divides? - Olusola Olafuyi; Nikita Parekh; Jacob Wright; Jennifer Koenig (Wiley, 2021)
Abstract Inter‐ethnic variability in pharmacokinetics (PK) has been attributed to several factors ranging from genetic to environmental. It is not clear how current teaching in higher education (HE) reflects what published literature suggests on this subject. This study aims to gain insights into current knowledge about inter‐ethnic differences in PK based on reports from published literature and current teaching practices in HE. A systematic literature search was conducted on PubMed and Scopus to identify suitable literature to be reviewed. Insights into inter‐ethnic differences in PK teaching among educators in HE and industry were determined using a questionnaire. Thirty‐one percent of the studies reviewed reported inter‐ethnic differences in PK, of these, 37% of authors suggested genetic polymorphism as possible explanation for the inter‐ethnic differences observed. Other factors authors proposed included diet and weight differences between ethnicities. Most respondents (80%) who taught inter‐ethnic difference in PK attributed inter‐ethnic differences to genetic polymorphism. While genetic polymorphism is one source of variability in PK, the teaching of genetic polymorphism is better associated with interindividual variabilities rather than inter‐ethnic differences in PK as there are no genes with PK implications specific to any one ethnic group. Nongenetic factors such as diet, weight, and environmental factors, should be highlighted as potential sources of interindividual variation in the PK of drugs.